1999
DOI: 10.1063/1.370232
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic mesostructure of giant magnetostrictive spring magnet type multilayers

Abstract: The magnetic behavior of giant magnetostrictive TbFe/FeCo multilayers show that individual layers of as-deposited multilayers in their demagnetized state are single domain due to stray-field coupling between adjacent layers. Such multilayers do not show a collective behavior during magnetization reversal. In contrast, stress-free films obtained by annealing at 543 K for 1 h subdivide themselves into multiple domains to lower their overall energy, and show a collective magnetization behavior. An interesting obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Very few investigations of domains in magnetostrictive multilayers are known. Chopra and co-workers [20] showed that in their demagnetized state individual layer of as deposited TbFe/CoFe are single domain due to stray field coupling between adjacent layers. Our measurements and direct observations, on the contrary, show that all layers are connected together by magnetic exchange and the magnetization in the whole stack of the layers turns as a single magnetic vector.…”
Section: +7°fmentioning
confidence: 99%
“…Very few investigations of domains in magnetostrictive multilayers are known. Chopra and co-workers [20] showed that in their demagnetized state individual layer of as deposited TbFe/CoFe are single domain due to stray field coupling between adjacent layers. Our measurements and direct observations, on the contrary, show that all layers are connected together by magnetic exchange and the magnetization in the whole stack of the layers turns as a single magnetic vector.…”
Section: +7°fmentioning
confidence: 99%
“…The ICC technique is readily able to detect changes in the buried layer, as shown previously in Ref. 9. Other aspects of the ICC method are given elsewhere.…”
Section: Methodsmentioning
confidence: 84%
“…Further results on structure and magnetic behavior are given elsewhere. [5][6][7][8][9] The results on the FePd system are preliminary in nature, and detailed studies will be reported in a later manuscript. The FePd and FePd/ Fe multilayers were deposited by dc magnetron sputtering in Ar pressure ranging from 3 mTorr to 10 mTorr and power from 30 to 120 W. The composition of the FePd films was varied either by sputtering Fe-30 at.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…A partir da medida da figura 33 foi calculado o coeficiente de magnetostricção do filme de Tb25Fe75 fabricado aplicando a equação 3.1. Os valores assumidos na equação foram ES = 169 GPa, EF = 50 GPa, S = 0,064, F = 0,30 (CHOPRA, et al, 1999) e L = 9.40mm. Os dados foram obtidos na literatura para o substrato de silício com filme amorfo de Tb25Fe75.…”
Section: Medidas De Deflexão Vertical Da Amostra E Cálculo Do Coeficiunclassified